Optimum sub-megawatt electric-hybrid power source selection. Issue 5 (23rd March 2020) - Picard, Benoit; Picard, Mathieu; Plante, Jean-Sébastien; Rancourt, David
Abstract : Purpose: The limited energy density of batteries generates the need for high-performance power sources for emerging eVTOL applications with radical operational improvement potential over traditional aircraft. This paper aims to evaluate on-design and off-design recuperated turbogenerator performances based on newly developed compression loaded ceramic turbines, the Inside-out Ceramic Turbine (ICT), in order to select the optimum engine configuration for sub-megawatt systems. Design/methodology/approach: System-level thermal engine modeling is combined with electric generators and power electronics performance predictions to obtain the Pareto front between efficiency and power density for a variety of engine designs, both for recuperated and simple cycle turbines. Part load efficiency for those engines are evaluated, and the results are used for an engine selection based on a simplified eVTOL mission capability. Findings: By operating with high turbine inlet temperature, variable output speed and adequately sized recuperator, a turbogenerator provides exceptional efficiency at both nominal power and part load operation for a turbomachine, while maintaining the high power density required for aircraft. In application with a high peak-to-cruise power ratio, such power source would provide eight times the range of battery-electric power pack and an 80% improvement over the state-of-the-art simple cycle turbogenerator. Practical implications: The implementation of a recuperator would provide additional gains especially important for military and on-demand mobility applications, notably reducing the heat signature and noise of the system. The engine low-pressure ratio reduces its complexity and combined with the fuel savings, the system could significantly reduce operational cost. Originality/value: Implementation of radically new ICT architecture provides the key element to make a sub-megawatt recuperated turbogenerator viable in terms of power density. The synergetic combination of a recuperator, high temperature turbine and variable speed electric generator provides drastic improvement over simple-cycle turbines, making such a system highly relevant as the power source for future eVTOL applications.